Who Demands Labour (De)Regulation in the Developing World? Insider–Outsider Theory Revisited - Lucas Ronconi; Ravi Kanbur; Santiago López-Cariboni (Institute of Labor Economics (IZA), 2019)
Contrary to the predictions of the insider–outsider model, we show that the large majority of outsiders in developing countries support, rather than oppose, protective labour regulations. This evidence holds across countries in different regions, across different types of protective labour regulations (i.e. severance payment, minimum wages, working time), and for different categories of outsiders (i.e. unemployed workers and employees without access to legally mandated labour benefits). We revise the economic and political assumptions of the insider–outsider model, discussing their empirical relevance in a developing country context.
Keywords: J4; J8; O17; 330; informal; labour; segmentation; monopsony; fairness